DYANGGO AND SAMBALI RITUAL DANCES OF CAGAYAN: AN ANALYSIS - Ramos , Chita C. (International Journal of Psychosocial Rehabilitation, 2020)
This study documented and analyzed two unpublished ritual Cagayan dances. In pursuance of this task, the Sambali and Dyanggo dances were documented, their characteristics were described in terms of historical background, costumes, props, musical accompaniment, and dance movements. The cultural traits of the Cagayano revealed in these dances were analyzed and the dominant concepts found in the dances were described. The data about the dances were provided using the interview. Documentary and thematic analyses of each ritual dance were made to determine the characteristics of each ethnic group. The study found out that the focus of these dances was all about Cagayano turned Christians, and reflect the way of life of the Cagayano and their values. As revealed in the findings, Cagayan ritual dances portray the Cagayano cultural values like courage, determination, charity and humanitarian attitude or brotherhood and religiosity. However, the Cagayan ritual dances have partially suffered loss of authenticity due to modification of costumes and props. Furthermore, Cagayan’s cultural ethnic tribes have cultural traits and practices that are distinct from other ethnic tribes in the Philippines. It is likewise found out that the two dances depict the ritual peoples’ reluctance to embrace Christianity but later faithfully accepted it.